Gender Related Differences in Career Patterns of Principals in Alabama - Spencer, William A.; Kochan, Frances K. (Education Policy Analysis Archives, 2000)
The purpose of this research was to determine the status of women administrators in the Alabama in terms of demographic and career patterns. A survey was sent to all principals in Alabama. Five hundred-fifty, or 42% of the principals responded. In Alabama, women principals are generally more recent in their position, are somewhat more likely to have come directly from the classroom, and have less mobility in acquiring the position.